SPECIFICATION OF DEMANDS FOR INNOVATION OF VOCATIONAL TRAINING IN THE CAR REPAIR STUDY BRANCH - ZATKALIK, Martin; HASKOVA, Alena (Trends in education, 2013)
Content angle and quality level of vocational training of labour power for car repair services has been criticised by the employers already in the long term. To achieve a change of this state, proper innovations related to both educational content and teaching processes offered by the corresponding secondary schools should be carried out. In order to design and consequently to carry out these innovations, it is necessary first and foremost to specify up-todate requirements of employers on the professional competency of the appropriate study branch graduates. The paper presents and discusses results of a survey aimed at these requirements finding out. On the basis of the survey results one can state that the main problem of the current vocational training is a need to innovate its content angle.
Keywords: car repair study branch; vocational training innovation; requirements of practice and employers; assessment of importance of competence profile components